Sleep, death, and rebirth: mystical practices of Lurianic Kabbalah - Ish-Shalom, Zvi (New perspectives in post-Rabbinic Judaism, 2021)
"In the sixteenth century, the famous kabbalist Isaac Luria transmitted a secret trove of highly complex mystical practices to a select groups of students. These meditations were designed to capitalize on sleep and death states in order to effectively split one's soul into multiple parts, and which, when properly performed, permitted the adept to free oneself from the cycle of rebirth. Through an in-depth analysis of these contemplative practices within the broader context of Lurianic literature, Zvi Ish-Shalom guides us on a penetrating scholarly journey into a realm of mystical teachings and practices never before available in English, illuminating a radically monistic vision of reality at the heart of Kabbalistic metaphysics and practice"--